The Effectiveness of Multimedia Application in Teaching Vocabularies for the Children in Rural Area - Norhayati; Nang Randu Utama (ENLIT, 2021)
Multimedia usage has been becoming a good trend in language learning. The collaboration of application developers and educational practitioners has created many multimedia applications with various learning purposes. This study was purposed to determine the effectiveness of multimedia applications to improve students’ vocabularies. The interesting variable of this study was the subject. The subject is the children who live in the village near Rungan river bank, namely Petuk Katimpun village. It is located in a rural area, located about 25 kilometers from Palangka Raya city. Those children have limited access to the latest gadgets or e-learning applications, so the children got new experiences of learning language by conducting this study. The study results showed some positive effects of the use of multimedia applications for children in basic language learning. The children can recall their memory perfectly when they were tested on a vocabulary quiz. The children were also can imitate the pronunciation of the words given 80% correctly. However, for dictation, the children still found it difficult to write down the words they heard correctly. Overall, the multimedia application usage for teaching vocabularies is very beneficial for the children.